2003
DOI: 10.2166/wst.2003.0609
|View full text |Cite
|
Sign up to set email alerts
|

Polyhydroxyalkanoate form and polyphosphate regulation: keys to biological phosphorus and glycogen transformations?

Abstract: Experimental studies with both synthetic and real domestic wastewater showed that poly-3-hydroxy-butyrate (3HB) and poly-3-hydroxy-valerate (3HV) formed in direct proportion to the acetate/propionate (Ace/Pro) ratio of the influent wastewater during Enhanced Biological Phosphorus Removal (EBPR). Acetic acid resulted in higher anaerobic phosphorus (P) release, polyhydroxyalkanoate (PHA) yield, 3HB content, and glycogen (CH) degradation. Linear regression showed that anaerobic P release (Prel) and CH degradation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Concentrations of readily biodegradable COD, such as short-chain fatty acids (SCFAs), in wastewater strongly affect the efficiency of biological nutrient (phosphorus and nitrogen) removal processes. SCFAs, such as acetic and propionic acids, have been demonstrated to be the most suitable substrates to support enhanced biological phosphorus removal (EBPR) ( ). It has been reported that 6−9 mg of SCFAs is required for biological removal of 1 mg of phosphorus ( ).…”
Section: Introductionmentioning
confidence: 99%
“…Concentrations of readily biodegradable COD, such as short-chain fatty acids (SCFAs), in wastewater strongly affect the efficiency of biological nutrient (phosphorus and nitrogen) removal processes. SCFAs, such as acetic and propionic acids, have been demonstrated to be the most suitable substrates to support enhanced biological phosphorus removal (EBPR) ( ). It has been reported that 6−9 mg of SCFAs is required for biological removal of 1 mg of phosphorus ( ).…”
Section: Introductionmentioning
confidence: 99%
“…between PAOs and GAOs have been carried out during the last 10 years. In virtually all cases it was confirmed that better bio-P performance was obtained with propionate, or a mix of propionate and acetate, than with acetate alone (Levantesi et al 2002;Randall & Liu 2002;Randall et al 2003;Chen et al 2004;Oehmen et al 2004;Pijuan et al 2004;Oehmen et al 2005b;Lu et al 2006;Oehmen et al 2006b). …”
Section: Resultsmentioning
confidence: 79%
“…A possible reason was that SOP removal was determined by SOP release and uptake. Moreover, SOP release was connected with wastewater acetic and propionic acid content, and SOP uptake was associated with both PHA degradation and SOP release [35]. The data in Fig.…”
Section: Relationship Between Pha Transformation and Tn Removal Efficmentioning
confidence: 84%